Cytochrome P450 1B1 Contributes to the Development of Atherosclerosis and Hypertension in Apolipoprotein E–Deficient Mice. Issue 1 (January 2016) - Song, Chi Young; Ghafoor, Khuzema; Ghafoor, Hafiz U.; Khan, Nayaab S.; Thirunavukkarasu, Shyamala; Jennings, Brett L.; Estes, Anne M.; Zaidi, Sahar; Bridges, Dave; Tso, Patrick; Gonzalez, Frank J.; Malik, Kafait U.
Abstract : Cytochrome P450 (CYP) 1B1 contributes to vascular smooth muscle cell growth and hypertension in male mice. This study was conducted to determine the contribution of CYP1B1 to the development of atherosclerosis and hypertension and associated pathogenesis in 8-week-old male apolipoprotein E–deficient ( ApoE −/− /Cyp1b1 +/+ ), and ApoE- and CYP1B1-deficient ( ApoE −/− /Cyp1b1 −/− ) mice fed a normal or atherogenic diet for 12 weeks. A separate group of ApoE −/− /Cyp1b1 +/+ mice on an atherogenic diet was injected every third day with the CYP1B1 inhibitor, 2, 3′, 4, 5′-tetramethoxystilbene (300 μg/kg), or its vehicle, dimethyl sulfoxide (30 μL, IP); systolic blood pressure was measured by the tail cuff method. After 12 weeks, mice were euthanized, blood collected for lipid analysis, and aortas harvested for measuring lesions and remodeling, and for infiltration of inflammatory cells by histological and immunohistochemical analysis, respectively, and for reactive oxygen species production. Blood pressure, areas of lipids and collagen deposition, elastin breaks, infiltration of macrophages and T lymphocytes, reactive oxygen species generation in the aorta, and plasma lipid levels were increased in ApoE −/− /Cyp1b1 +/+ mice on an atherogenic diet; these changes were minimized in mice given 2, 3′, 4, 5′-tetramethoxystilbene, and in ApoE −/− /Cyp1b1 −/− mice on an atherogenic diet; absorption/production of lipids remained unaltered in these mice. These data suggest that aortic lesions, hypertension, and associated pathogenesis in ApoE −/− /Cyp1b1 +/+ mice on an atherogenic diet are most likely dependent on CYP1B1-generated oxidative stress and increased plasma lipid levels independent of blood pressure and absorption of lipids. CYP1B1 could serve as a novel target for developing drugs to treat atherosclerosis and hypertension caused by hypercholesterolemia. Abstract : Supplemental Digital Content is available in the text.